Adecuación de la indicación de la colonoscopia según criterios de EPAGE II en un hospital universitario de Uruguay - Rodrigo Dorelo; Soledad Francia; Joaquín Berrueta; Alicia Aleman; Carolina Olano (Universidad Nacional Hermilio Valdizán, 2021)
Background: Prioritization of criteria have been developed to reduce the increased demand. The European Society for Gastrointestinal Endoscopy developed an online program (EPAGE II). The aim of this study is to evaluate the appropriateness of the colonoscopy indication according to the EPAGE II criteria and correlate it with the endoscopic findings. Materials and Methods: Retrospective and analytical study that included all colonoscopies performed in the period March 2018 - March 2019. Colonoscopies with insufficient preparation and missing data, were excluded. They were categorized into having appropriate, inappropriate and uncertain indication, according to EPAGE II criteria. Sociodemographic data, indication, degree of preparation, and the presence of relevant findings were recorded. Results: 648 studies were included, 64.7% were women, and 51.8% were ordered by gastroenterologists. In 62% the preparation was adequate. In 171 (26.4%) the indication was CCR screening. In 525 (81%) the indication was appropriate, in 79 (12,2%) was not appropriate and in 44 (6,8%) was uncertain. An appropriate indication was significantly associated with age older than 50 years (p≤0.001). An endoscopic relevant diagnosis was observed in 55.2%. There was a significant association between appropriate indication and a relevant endoscopic diagnosis (p <0.01). The sensitivity, specificity, PPV and NPV of EPAGE II for an appropriate indication in relation to a relevant endoscopic finding were 84.92 %, 24.14%, 69.72% and 43.75% respectively. Conclusions: In this group of patients the EPAGE II showed high sensitivity and low specificity for the appropriateness of the indication in relation to the findings.